Discover answers to your most pressing questions at Westonci.ca, the ultimate Q&A platform that connects you with expert solutions. Ask your questions and receive accurate answers from professionals with extensive experience in various fields on our platform. Discover in-depth answers to your questions from a wide network of professionals on our user-friendly Q&A platform.
Sagot :
Given the line in point slope form:
y + 1 = 3(x - 2)
Let's rewrite the equation in slope intercept form.
Using the point slope form:
y - y1 = m(x - x1)
Thus, we have the following:
x1 = -2
y1 = 1
slope, m = 3
To write in slope intercept form, all you have to do is to isolate the y.
Thus,
y + 1 = 3(x - 2)
Expand the parenthesis:
y + 1 = 3x - 6
Subtract 1 from both sides:
y + 1 - 1 = 3x - 6 - 1
y = 3x - 6 - 1
y = 3x - 7
Therefore, the equation in slope intercept form is:
y = 3x - 7
ANSWER:
y = 3x - 7
Thanks for using our service. We're always here to provide accurate and up-to-date answers to all your queries. We hope you found this helpful. Feel free to come back anytime for more accurate answers and updated information. Thank you for using Westonci.ca. Come back for more in-depth answers to all your queries.